Effects of Nb promoter on the properties of Cu/ZnO/SBA-15 catalyst and performance in methanol production - Noor, A.M.Z. (Trans Tech Publications Ltd, 2016)
Hydrogenation of CO2 provides an alternative route for methanol production and attractive option for CO2 utilization. The present work investigates the synthesis of Cu-based catalyst on mesoporous silica (SBA-15) and promotion of the Cu-based catalyst with niobium (Nb). The addition of Nb promoter enhanced the reducibility and dispersion of the active sites as well as increased the BET and Cu surface areas. The performance of the synthesized catalyst in the hydrogenation of CO2 was evaluated in a fixed-bed microreactor at 523K, 22.5bar and H2/CO2 of 3. The CO2 conversion using the Cu/ZnO/SBA-15 catalyst was 14.2 and increased to 17.1 on the Nb-promoted catalyst. The yield of methanol obtained using the un-promoted Cu-based catalyst was 51.4 g/h.gcat and it increased to 143 g/h.gcat over the Nb-promoted catalyst. Â© 2016 Trans Tech Publications, Switzerland.